Clinical and functional status of patients with severe COVID-19 pneumonia: an observational study at 2–3 months following discharge - Castillo Sánchez, Inmaculada; Camarasa, Julia Tárrega; Barbeta Sánchez, Enric; Oliveira, Vinicius Rosa (Frontiers in Rehabilitation Sciences, 2023)
Introduction Critically ill COVID-19 patients present long-term sequelae that affect their everyday life. This study aimed to describe the clinical and functional status of patients with severe COVID-19 pneumonia at 2–3 months post discharge from a Spanish critical care unit. Methods We collected retrospective data from 58 patients admitted to the critical care unit with diagnosis of severe respiratory failure due to COVID-19. Only patients who required invasive (IMV) or noninvasive ventilation (NIV) during their hospital stay were included. The following data were collected 2–3 months after hospital discharge: respiratory signs and symptoms, lung ultrasound (LUS) and diaphragm ultrasound images, blood test analysis, lung function parameters (spirometry and DLCO), exercise capacity (6 min walk test and sit-to-stand test), level of physical activity and health-related quality of life. Results We found clinical symptoms and lung structural alterations in LUS images of 26 patients (48.1%). Those presenting LUS abnormalities had longer length of stay in hospital (p = 0.026), functional alterations in spirometry (p < 0.01) and decreased diaphragm excursion (p = 0.029). No significant alterations were observed in blood test analysis, exercise capacity, level of physical activity and health-related quality of life. Conclusions A significant part of the patients admitted to a critical care unit continue to present clinical symptoms, pulmonary morphological abnormalities, and lung function alterations 2–3 months post discharge. This study corroborates that assessing the functional status of the survivors is essential to monitor the evolution of pulmonary sequelae.